Analysis of the type II-A CRISPR-Cas system of Streptococcus agalactiae reveals distinctive features according to genetic lineages - Lier, Clément; Baticle, Elodie; Horvath, Philippe; Haguenoer, Eve; Valentin, Anne-Sophie; Glaser, Philippe; Mereghetti, Laurent; Lanotte, Philippe (Frontiers in Genetics, 2015)
CRISPR-Cas systems (clustered regularly interspaced short palindromic repeats/CRISPR-associated proteins) are found in 90% of archaea and about 40% of bacteria. In this original system, CRISPR arrays comprise short, almost unique sequences called spacers that are interspersed with conserved palindromic repeats. These systems play a role in adaptive immunity and participate to fight non-self DNA such as integrative and conjugative elements, plasmids, and phages. In Streptococcus agalactiae, a bacterium implicated in colonisation and infections in humans since the 1960s, two CRISPR-Cas systems have been described. A type II-A system, characterised by proteins Cas9, Cas1, Cas2 and Csn2, is ubiquitous, and a type I-C system, with the Cas8c signature protein, is present in about 20% of the isolates. Unlike type I-C, which appears to be non-functional, type II-A appears fully functional. Here we studied type II-A CRISPR-Cas loci from 126 human isolates of S. agalactiae belonging to different clonal complexes that represent the diversity of the species and that have been implicated in colonisation or infection. The CRISPR-Cas locus was analysed both at spacer and repeat levels. Major distinctive features were identified according to the phylogenetic lineages previously defined by multilocus sequence typing, especially for the Sequence Type (ST) 17, which is considered hypervirulent. Among other idiosyncrasies, ST-17 shows a significantly lower number of spacers in comparison with other lineages. This characteristic could reflect the peculiar virulence or colonisation specificities of this lineage.